Inceasing The Class Of UMKM In The Plut KUKKM DIY Business Incubation Program 2019 - Utomo, Yuana Tri; Lina, Lina Susanti (Magna: Journal of Economics, Management, and Business, 2022)
The business incubation program is one of the programs organized by PLUT KUMKM DIY with the hope of growing new entrepreneurs, assisting in business development in the form of mentoring and training to improve business towards MSMEs upscale. This study aims to see the increase in business experienced by tenants in eight aspects after participating in the business incubation program in 2019. This type of research uses a qualitative approach. Data sources are obtained from the results of in-depth interviews, observations, documentation and other supporting data. All data was analyzed using Miles and Hubermen analysis with the validity of the data through triangulation of data collection methods. Based on the results of the study, it is known that there are improvements in the eight aspects analyzed. Each tenant with its various stages has improved in different aspects so that this program can help business actors towards MSMEs move up in class.